A kind of thermal conductive and insulating water-based polyurea coating and preparation method thereof

By adding modified silicon carbide whiskers, boron nitride nanosheets and aluminum nitride nanoparticles to the aqueous polyurea coating, a three-dimensional thermal conductivity network and micro-nano layered structure are formed, which solves the problem of poor hydrophobic effects of water-based coatings in anti-condensation, and improves efficient thermal conductivity, insulation, hydrophobicity and wear resistance.

CN118620503BActive Publication Date: 2025-04-04STATE GRID JIANGSU ELECTRIC POWER CO LIANYUNGANG POWER SUPPLY CO +1

Patent Information

Application Number
CN202411099298.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-12
Publication Date
2025-04-04
Estimated Expiration
2044-08-12

AI Technical Summary

Technical Problem

In the prior art, water-based coatings have poor hydrophobic effects in anti-condensation, weak anti-pollution effects, and are not environmentally friendly.

Method used

Using a thermally insulated aqueous polyurea coating, the thermal conductivity, insulation, hydrophobic properties and wear resistance of the coating are improved by adding modified silicon carbide whiskers, modified boron nitride nanosheets and modified aluminum nitride nanoparticles to the polyurea emulsion.

Benefits of technology

It realizes the efficient thermal conductivity and insulation properties of the coating, while improving the hydrophobic and wear resistance of the coating, reducing production costs, and improving environmental friendliness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118620503B_ABST
    Figure CN118620503B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of coating technology, and specifically discloses a thermally conductive insulating water-based polyurea coating and a preparation method thereof, wherein the water-based polyurea coating comprises the following raw materials in parts by weight: 83 to 91 parts of polyurea emulsion, 8 to 15 parts of mixed fillers, and 1 to 2 parts of dispersants. The present invention also discloses a preparation method for the thermally conductive insulating water-based polyurea coating, which is prepared by modifying fillers of various sizes and morphologies, and then sequentially mixing the fillers with resin materials to ensure the dispersion effect between the raw materials. Compared with the prior art, the water-based polyurea coating obtained by the present invention not only has the characteristics of existing insulating coatings, but also has strong thermal conductivity, hydrophobicity and wear resistance, can be used in a variety of power equipment, and has good market prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coatings, and in particular relates to a thermally conductive and insulating water-based polyurea coating and a preparation method thereof. Background Art

[0002] The growing demand for electricity in modern society has put forward higher requirements for the smooth operation of power equipment. Applying organic coatings on power equipment can effectively improve the insulation and waterproof performance of power equipment, and resist the damage to power equipment caused by condensation and other phenomena. Water-based paint is a new type of environmentally friendly paint. Compared with traditional paints, it has the characteristics of no solvent, fast curing, insensitivity to humidity and temperature, short construction period, excellent high temperature resistance and aging resistance, and is environmentally friendly. Therefore, it has developed rapidly in recent years and has been used in many industries such as electricity.

[0003] For example, a Chinese patent document with publication number CN 104693968 A discloses a high thermal conductivity and heat dissipation coating and a preparation method thereof, which utilizes carbon materials with high thermal conductivity and emissivity as the main heat dissipation medium and heat transfer channel, and evenly disperses them in a water-based resin to prepare a coating, and the heat is transferred to the coating, and the coating then dissipates the heat into the space to improve the heat dissipation effect; another example is a Chinese patent document with publication number CN 105153906 A discloses a water-based polyurethane functional coating and a preparation method thereof, and the water-based coating can achieve high volume content addition of nano-carbon materials to achieve regulation of the electrical and thermal conductivity of the coating; another example is a water-based acrylic ester thermal conductive coating and a preparation method thereof, and the thermal conductive coating uses acrylic ester copolymer emulsion as a base material, and inorganic particles with high thermal conductivity such as aluminum oxide, zinc oxide, aluminum nitride, boron nitride, carbon nanotubes, and graphene as thermal conductive fillers, and the thermal conductivity of the prepared product reaches 0.95W / m·K.

[0004] However, the above technical solutions all achieve the improvement of the thermal conductivity of the coating by adding thermally conductive fillers to the resin base material, but the high thermal conductivity fillers will also cause damage to the electrical insulation performance of the coating and cause high costs due to the large amount of addition.

[0005] Prior art document 1 (CN107641424A) discloses a boron nitride nanosheet-enhanced thermally conductive insulating water-based coating and its preparation and use methods. It is composed of a mixture of component I and component II, the weight ratio of component I to component II is 100:58-65, and the preparation steps are: preparing component I; mixing component I and component II. However, the shortcomings of this existing document are: 1. Boron nitride is large in size and lacks a size gradient, and cannot form a three-dimensional thermal conductive network like the present invention, and the thermal conductivity effect is poor; 2. Using only boron nitride, the formed coating has insufficient wear resistance and cannot form a micro-nano layered structure at the interface, and the hydrophobic performance is poor.

[0006] Prior art document 2 (CN109181511B) discloses a high thermal conductivity insulating water-based coating, including a water-based emulsion and an additive, and also including a high thermal conductivity insulating filler; the high thermal conductivity insulating filler is divided into a nano-scale filler and a micro-scale filler, and the mass ratio of the nano-scale filler to the micro-scale filler is 0.1 to 10:1; the high thermal conductivity insulating filler includes at least nitride. However, the shortcomings of this existing document are: 1. The micro-nano material has not been modified, and there will be uneven distribution in the emulsion, especially the micro-scale material; 2. The addition step is not mentioned in the prior art, and the actual addition step will significantly affect the distribution of the micro-nano material, affecting the hydrophobicity and wear resistance of the coating. Summary of the invention

[0007] In order to solve the deficiencies in the prior art, the present invention provides a thermally conductive and insulating water-based polyurea coating and a preparation method thereof, which solves the problems of poor hydrophobic effect, weak anti-pollution effect and environmental unfriendliness of current anti-condensation coatings.

[0008] The present invention adopts the following technical solution.

[0009] The first aspect of the present invention discloses a thermally conductive and insulating waterborne polyurea coating, the waterborne polyurea coating comprising the following raw materials in parts by weight: 83 to 91 parts of polyurea emulsion, 8 to 15 parts of mixed filler and 1 to 2 parts of dispersant;

[0010] The polyurea emulsion comprises: polyetheramine, diisocyanate, chain extender and end-capping agent, wherein the molar mass ratio of the polyetheramine, diisocyanate, chain extender and end-capping agent is 1.5-2.5:4:1:2;

[0011] The mixed filler comprises: modified silicon carbide whiskers, modified boron nitride nanosheets and modified aluminum nitride nanoparticles.

[0012] Preferably, the diisocyanate is any one of toluene diisocyanate, 4,4' diphenylmethane diisocyanate or isophorone diisocyanate, or a combination of two or more thereof;

[0013] The chain extender is any one of diethyltoluenediamine, 3,3'-dichloro-4,4'-diaminodiphenylmethane, dimethylthiotoluenediamine, and N,N'-dialkylmethyldiamine;

[0014] The blocking agent is any one of ethyl isocyanate acrylate or pentaerythritol triacrylate.

[0015] The mass ratio of modified silicon carbide whiskers, modified boron nitride nanosheets and modified aluminum nitride nanoparticles added in the mixed filler is 1-4:3-5:4-6.

[0016] Preferably, the length of the silicon carbide whiskers in the modified silicon carbide whiskers is 10 to 20 μm and the diameter is 500 to 1000 nm;

[0017] The boron nitride nanosheets in the modified boron nitride nanosheets have a thickness of 50 to 200 nm and a sheet diameter of 500 nm to 2 μm;

[0018] The diameter of the aluminum nitride nanoparticles in the modified aluminum nitride nanoparticles is 50 to 100 nm.

[0019] Preferably, the modified material of the modified silicon carbide whisker is diisocyanate, and the diisocyanate is any one of toluene diisocyanate, 4,4' diphenylmethane diisocyanate or isophorone diisocyanate, or a combination of two or more thereof;

[0020] The modified material of the modified boron nitride nanosheets and modified aluminum nitride nanoparticles is a silane coupling agent, and the silane coupling agent is one of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, and γ-aminoethylaminopropyltrimethoxysilane, or a combination of two or more thereof.

[0021] The second aspect of the present invention discloses a method for preparing a thermally conductive insulating waterborne polyurea coating, based on the thermally conductive insulating waterborne polyurea coating, comprising the following steps:

[0022] S1 filler modification: weigh boron nitride nanosheets, aluminum nitride nanoparticles and silicon carbide whiskers and put them into a container, and react under set conditions to obtain modified boron nitride nanosheets, modified aluminum nitride nanoparticles and modified silicon carbide whiskers;

[0023] S2: preparing polyurea emulsion: weighing polyetheramine into a container, adding solvent to dissolve, then dropping diisocyanate to react, and then dropping chain extender and end-capping agent to the container after the reaction is completed and continuing the reaction to obtain polyurea emulsion;

[0024] S3: Prepare coating: weigh polyurea emulsion into a container, add modified aluminum nitride nanoparticles and dispersant, and then ultrasonically treat, then add modified boron nitride nanosheets and dispersant, and then ultrasonically treat, finally add modified silicon carbide whiskers and dispersant, and then ultrasonically treat, after the ultrasonic treatment is completed, continue stirring to obtain a water-based polyurea coating.

[0025] Preferably, step S1 specifically includes:

[0026] S100: Weighing boron nitride nanosheets, aluminum nitride nanoparticles and a silane coupling agent, adding a solvent thereto for ultrasonic dispersion, heating and stirring after the ultrasonic dispersion ends, washing and drying after the reaction ends to obtain modified boron nitride nanosheets and modified aluminum nitride nanoparticles;

[0027] S200: Weighing silicon carbide whiskers, adding a mixed solvent thereto and stirring until the silicon carbide whiskers are completely dissolved, then dropping diisocyanate thereto and continuing the reaction, and after the reaction is completed, centrifugally washing and drying to obtain modified silicon carbide whiskers;

[0028] Preferably, in the step S100, the solvent is 50% ethanol, the ultrasonic time is 20 to 30 min, the stirring temperature is 55 to 65°C, the stirring time is 12 to 24 h, the drying temperature is 55 to 65°C, and the drying time is 12 to 24 h; in the step S200, the mixed solvent is water and acetone, the reaction temperature is 30 to 35°C, and the reaction time is 30 min to 45 min.

[0029] Preferably, in step S2, the isophorone diisocyanate dropping speed is 1 to 2 s / drop, the reaction temperature is 0 to 10° C., and the reaction time is 30 to 60 min;

[0030] The chain extender dropping speed is 1-2s / drop, the reaction temperature is 0-10°C, and the reaction time is 30-60min.

[0031] Preferably, in step S3, the ultrasonic time is 15 to 30 minutes, and the stirring reaction time is 1 to 2 hours.

[0032] The beneficial effect of the present invention is that, compared with the prior art,

[0033] 1) The present invention dopes a variety of micro-nano fillers of different morphologies into the original resin material, including silicon carbide whiskers, boron nitride nanosheets and aluminum nitride nanoparticles. By modifying the three micro-nano fillers, they can be evenly dispersed in the resin material, and rely on the excellent thermal conductivity and insulation coefficient of the fillers to improve the thermal conductivity and insulation properties of the resulting coating. At the same time, the three micro-nano fillers have different sizes and morphologies. The larger silicon carbide whiskers are dispersed in the resin to construct a basic thermal conduction path. Nano-scale boron nitride and aluminum nitride can be filled in the silicon carbide whiskers and the resin material, and the mutually dispersed silicon carbide whiskers are connected, finally forming a three-dimensional, interconnected thermal conduction network, so that the coating has a better heat dissipation effect.

[0034] 2) In the present invention, the boron nitride nanosheets and aluminum nitride nanoparticles are modified with hydrophobic groups. When the nanomaterials are dispersed in the polyurea resin, the silane coupling agent can reduce the coating surface energy of the coating, so that the coating has good hydrophobic properties. The size of the silicon carbide whiskers modified by diisocyanate can reach the micron level. When the nano-scale boron nitride nanosheets and aluminum nitride nanoparticles are fully mixed in the resin material containing silicon carbide whiskers, the boron nitride nanosheets and aluminum nitride nanoparticles tend to cover the surface of the silicon carbide whiskers modified by diisocyanate to form a micro-nano layered structure, which can significantly improve the roughness and wear resistance of the coating, increase its static contact angle, make the coating exhibit super hydrophobic properties and improve its wear resistance.

[0035] 3) The present invention adopts a step-by-step mixing and adding process when preparing the coating. First, small-sized boron nitride nanosheets and aluminum nitride nanoparticles are added to form a "sea-island structure" in the emulsion, and then the silicon carbide whiskers modified with diisocyanate are added last, so that the large-sized silicon carbide whiskers act as a bridge to connect the boron nitride nanosheets and aluminum nitride nanoparticles, thereby ensuring that all fillers can be evenly dispersed in the polyurea emulsion, and can form a complete heat conduction path and micro-nano layered structure, thereby improving the comprehensive performance of the material. At the same time, the thermal conductivity and wear resistance of the coating can be improved with less filler material, and the electrical insulation performance of the coating is not lost, thereby reducing the production cost of the coating. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 is a SEM image of the silicon carbide whisker of the present invention;

[0037] Figure 2 is a SEM image of the boron nitride nanosheets in the present invention;

[0038] Figure 3 This is a TEM image of aluminum nitride nanoparticles in the present invention. DETAILED DESCRIPTION

[0039] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. The embodiments described in this application are only part of the embodiments of the present invention, not all of them. Based on the spirit of the present invention, other embodiments obtained by ordinary technicians in this field without creative work are all within the scope of protection of the present invention.

[0040] Example 1

[0041] The present embodiment provides a thermally conductive and insulating water-based polyurea coating, comprising the following raw materials in parts by weight: 87.5 parts of polyurea emulsion, 11 parts of mixed filler and 1.5 parts of dispersant. The polyurea emulsion comprises polyetheramine, diisocyanate, chain extender and end capping agent. In the present embodiment, the diisocyanate is isophorone diisocyanate, the chain extender is diethyltoluenediamine, and the end capping agent is ethyl isocyanate acrylate. The molar mass ratio of polyetheramine, diisocyanate, chain extender and end capping agent is 2:4:1:2.

[0042] like Figure 1-3 As shown, the mixed filler includes 2 parts of modified silicon carbide whiskers, 4 parts of modified boron nitride nanosheets and 5 parts of modified aluminum nitride nanoparticles.

[0043] This embodiment also provides a method for preparing a thermally conductive and insulating water-based polyurea coating, comprising the following steps:

[0044] S1 filler modification:

[0045] S100: Weighing boron nitride nanosheets and aluminum nitride nanoparticles respectively, adding a solvent to them to disperse them, adding a silane coupling agent to them after dispersion, ultrasonicating them, heating and stirring to react after the ultrasonication, washing and drying to obtain modified boron nitride nanosheets and modified aluminum nitride nanoparticles;

[0046] In a preferred but non-limiting embodiment of the present invention, the solvent is 50% ethanol, the ultrasonic time is 20 to 30 min, the stirring temperature is 55 to 65° C., the stirring time is 12 to 24 h, the drying temperature is 55 to 65° C., and the drying time is 12 to 24 h.

[0047] Specifically, 1g of boron nitride nanosheets and 1g of aluminum nitride nanoparticles are weighed respectively. The thickness of the boron nitride nanosheets is 50-400nm and the size is 500nm; the diameter of the aluminum nitride nanoparticles is 50-100nm. The boron nitride nanosheets and aluminum nitride nanoparticles are respectively put into a flask, 100ml of ethanol solution is added to the flask, and 0.1g of silane coupling agent is added respectively after ultrasonic dispersion for 5min. In this embodiment, the silane coupling agent is 3-aminopropyltriethoxysilane. After ultrasonication for 30min at room temperature, the temperature is heated to 60°C, and the reaction is stirred for 24h to allow the silane coupling agent to fully react with the boron nitride nanosheets and aluminum nitride nanoparticles. After the reaction is completed, the precipitate is filtered and washed with ethanol and water. After washing, it is dried in a constant temperature drying oven at 60°C for 2h to obtain modified boron nitride nanosheets and modified aluminum nitride nanoparticles, which are recovered for use.

[0048] It is worth noting that the three types of micro-nano fillers have different sizes and morphologies. The larger silicon carbide whiskers are dispersed in the resin to construct a basic thermal conductive path. Nano-scale boron nitride and aluminum nitride can be filled in the silicon carbide whiskers and resin materials, and connect the mutually dispersed silicon carbide whiskers, ultimately forming a three-dimensional, interconnected thermal conductive network, which enables the coating to have a better heat dissipation effect.

[0049] In addition, small-sized boron nitride nanosheets and aluminum nitride nanoparticles are added first to form a "sea-island structure" in the emulsion, and then the silicon carbide whiskers modified with diisocyanate are added last, so that the large-sized silicon carbide whiskers act as a bridge to connect the boron nitride nanosheets and aluminum nitride nanoparticles, thus ensuring that all fillers can be evenly dispersed in the polyurea emulsion.

[0050] S200: Weighing silicon carbide whiskers, adding a mixed solvent thereto and stirring until the silicon carbide whiskers are completely dissolved, then dropping diisocyanate thereto and continuing the reaction, and after the reaction is completed, centrifugally washing and drying to obtain modified silicon carbide whiskers;

[0051] In a preferred but non-limiting embodiment of the present invention, the mixed solvent in step S200 is water and acetone, the reaction temperature is 30-35° C., and the reaction time is 30 min-45 min.

[0052] Specifically, 0.1 g of silicon carbide whiskers were weighed and placed in a flask. The length of the silicon carbide whiskers was 10-20 μm and the diameter was 500-1000 nm. 15 ml of water and 35 ml of acetone were added to the flask, and ultrasonic dispersion was performed for 5 min while stirring was maintained. The temperature was raised to 30°C, and 1.5 g of IPDI (C 12 H 18 N2O2, isophorone diisocyanate), after the addition is completed, the reaction is maintained for 8 hours. After the reaction is completed, the precipitate is collected by centrifugation, washed with a water / acetone mixed solution, and then dried in a 70°C constant temperature oven for 48 hours to obtain modified silicon carbide whiskers for use.

[0053] S2: preparing a polyurea emulsion: weighing a polyetheramine, adding a solvent thereto to dissolve it, dropping a diisocyanate thereto to react, and after the reaction is completed, dropping a chain extender and a capping agent thereto and continuing the reaction to obtain an aqueous polyurea emulsion;

[0054] In a preferred but non-limiting embodiment of the present invention, in step S2, the diisocyanate is added at a rate of 1 to 2 s / drop, the reaction temperature is 0 to 10°C, and the reaction time is 30 to 60 min; the chain extender is added at a rate of 1 to 2 s / drop, the reaction temperature is 0 to 10°C, and the reaction time is 30 to 60 min.

[0055] Specifically, 0.01 mol of polyetheramine was weighed and added to a flask, 10 ml of acetone solution was added to the flask to dissolve, IPDI was added dropwise to the flask under nitrogen atmosphere at room temperature, the addition speed was 2 s / drop, and the total amount of addition was 0.02 mol. The reaction was stirred at 5°C for 30 min, and a sample was taken to test the -NCO content, and then a chain extender was added dropwise thereto, the addition speed was 2 s / drop, and the total amount of addition was 0.005 mol.

[0056] In this embodiment, diethyltoluenediamine is selected as the chain extender, and a sample is taken to test its -NCO content. After reaching the standard, 0.01 mol of the end-capping agent ethyl isocyanate acrylate is added thereto, and the reaction is continued until the -NCO content reaches the standard value. Water is added and sheared at high speed for 2 hours, and then rotary evaporation is performed to remove acetone to obtain a polyurea emulsion.

[0057] S3: Prepare coating: Weigh polyurea emulsion, add modified aluminum nitride nanoparticles and dispersant thereto, and then ultrasonically treat. Then, add modified boron nitride nanosheets and dispersant thereto, and then ultrasonically treat. Finally, add modified silicon carbide whiskers and dispersant thereto, and then ultrasonically treat. After the ultrasonic treatment, continue stirring to obtain a waterborne polyurea coating.

[0058] In a preferred but non-limiting embodiment of the present invention, the ultrasonic time in step S3 is 15 to 30 minutes, and the stirring reaction time is 1 to 2 hours.

[0059] Specifically, 87.5 parts of aqueous polyurea emulsion were weighed, 5 parts of modified aluminum nitride nanoparticles and 0.5 parts of dispersant were added thereto, and ultrasonic dispersion was performed for 15 minutes. After the ultrasonic dispersion was completed, 4 parts of modified boron nitride nanosheets and 0.5 parts of dispersant were added thereto, and ultrasonic dispersion was performed for 15 minutes. After the ultrasonic dispersion was completed, 2 parts of modified silicon carbide whiskers and 0.5 parts of dispersant were added thereto, and ultrasonic dispersion was performed for 15 minutes. After the ultrasonic dispersion was completed, stirring and dispersion were continued for 2 hours to obtain an aqueous polyurea coating.

[0060] Example 2

[0061] The difference between this embodiment and embodiment 1 is that the amount of polyetheramine added in the polyurea emulsion is different. Specifically, the molar mass ratio of polyetheramine, diisocyanate, chain extender and end capping agent in the polyurea emulsion is 1.5:4:1:2. Other components and preparation methods are the same as those in embodiment 1.

[0062] Example 3

[0063] The difference between this embodiment and embodiment 1 is that the amount of polyetheramine added in the polyurea emulsion is different. Specifically, the molar mass ratio of polyetheramine, diisocyanate, chain extender and end capping agent in the polyurea emulsion is 2.5:4:1:2. Other components and preparation methods are the same as those in embodiment 1.

[0064] Example 4

[0065] The difference between this embodiment and embodiment 1 is that the addition amount of the modified silicon carbide whisker, the modified boron nitride nanosheet and the modified aluminum nitride nanoparticle in the mixed filler and the mass ratio of the mixed filler to the polyurea emulsion are different, and the specific mass ratio of the modified silicon carbide whisker, the modified boron nitride nanosheet and the modified aluminum nitride nanoparticle is 2.5:4.5:5.5; the mass ratio of the mixed filler to the polyurea emulsion is 86:12.5. The other components and preparation method are the same as those in embodiment 1.

[0066] Example 5

[0067] The difference between this embodiment and embodiment 1 is that the addition amounts of the modified silicon carbide whiskers, modified boron nitride nanosheets and modified aluminum nitride nanoparticles in the mixed filler are different, and the specific addition mass ratio of the modified silicon carbide whiskers, modified boron nitride nanosheets and modified aluminum nitride nanoparticles is 4:3:4. The other components and preparation method are the same as those in embodiment 1.

[0068] Example 6

[0069] The difference between this embodiment and embodiment 1 is that the addition amount of the modified silicon carbide whisker, the modified boron nitride nanosheet and the modified aluminum nitride nanoparticle in the mixed filler and the mass ratio of the mixed filler to the polyurea emulsion are different, and the specific mass ratio of the modified silicon carbide whisker, the modified boron nitride nanosheet and the modified aluminum nitride nanoparticle is 1:5:7; the mass ratio of the mixed filler to the polyurea emulsion is 85.5:13. The other components and preparation method are the same as those in embodiment 1.

[0070] Comparative Example 1

[0071] The difference between this comparative example and Example 1 is that the amount of polyetheramine added in the polyurea emulsion is different. Specifically, the molar mass ratio of polyetheramine, diisocyanate, chain extender and end-capping agent in the polyurea emulsion is 0.5:4:1:2. Other components and preparation methods are the same as those in Example 1.

[0072] Comparative Example 2

[0073] The difference between this comparative example and Example 1 is that the amount of polyetheramine added in the polyurea emulsion is different. Specifically, the molar mass ratio of polyetheramine, diisocyanate, chain extender and end-capping agent in the polyurea emulsion is 3:4:1:2. Other components and preparation methods are the same as those in Example 1.

[0074] Comparative Example 3

[0075] The difference between this comparative example and Example 1 is that the addition amount of the modified silicon carbide whisker, the modified boron nitride nanosheet and the modified aluminum nitride nanoparticle in the mixed filler and the mass ratio of the mixed filler to the polyurea emulsion are different, and the specific mass ratio of the modified silicon carbide whisker, the modified boron nitride nanosheet and the modified aluminum nitride nanoparticle is 0.5:2:3; the mass ratio of the mixed filler to the polyurea emulsion is 93:5.5. The other components and preparation method are the same as those in Example 1.

[0076] Comparative Example 4

[0077] The difference between this comparative example and Example 1 is that the addition amount of the modified silicon carbide whisker, the modified boron nitride nanosheet and the modified aluminum nitride nanoparticle in the mixed filler and the mass ratio of the mixed filler to the polyurea emulsion are different, and the specific mass ratio of the modified silicon carbide whisker, the modified boron nitride nanosheet and the modified aluminum nitride nanoparticle is 5:6:8; the mass ratio of the mixed filler to the polyurea emulsion is 79.5:19. The other components and preparation method are the same as those in Example 1.

[0078] Comparative Example 5

[0079] The difference between this comparative example and Example 1 is that no modified silicon carbide is added to the mixed filler. In this comparative example, the mixed filler is modified boron nitride nanosheets and modified aluminum nitride nanoparticles, and the added mass ratio of modified boron nitride nanosheets and modified aluminum nitride nanoparticles is 5:6. Other components and preparation methods are the same as those in Example 1.

[0080] Comparative Example 6

[0081] The difference between this comparative example and Example 1 is that no modified boron nitride nanosheets are added to the mixed filler. In this comparative example, the mixed filler is modified silicon carbide and modified aluminum nitride nanoparticles, and the added mass ratio of modified silicon carbide and modified aluminum nitride nanoparticles is 4:7. The other components and preparation method are the same as those in Example 1.

[0082] Comparative Example 7

[0083] The difference between this comparative example and Example 1 is that no modified aluminum nitride nanoparticles are added to the mixed filler. In this comparative example, the mixed filler is modified silicon carbide and modified boron nitride nanosheets, and the added mass ratio of modified silicon carbide and modified boron nitride nanosheets is 4.5:6.5. The other components and preparation method are the same as those in Example 1.

[0084] Comparative Example 8

[0085] The difference between this comparative example and Example 1 is that the mixed fillers have not been modified. The specific preparation is as follows: weigh 0.01 mol of polyetheramine and add it to a flask, add 10 ml of acetone solution to the flask, and add IPDI to the flask under nitrogen atmosphere at room temperature. The drop rate is 2s / drop, and the total amount of drop is 0.02 mol. The reaction is stirred at 5°C for 30 minutes, and the -NCO content is tested and tested to meet the standard. Then, the chain extender is added thereto at a drop rate of 2s / drop, and the total amount of drop is 0.005 mol. In this embodiment, diethyltoluenediamine is selected as the chain extender. After the -NCO content is tested and met, 0.01 mol of isocyanate ethyl acrylate is added thereto, and the reaction is continued until the -NCO content reaches the standard value. After adding water and high-speed shearing for 2h, the polyurea emulsion is obtained after rotary evaporation to remove acetone. Weigh 87.5 parts of aqueous polyurea emulsion, add 5 parts of aluminum nitride nanoparticles and 0.5 parts of dispersant thereto, and ultrasonically disperse for 15 minutes. After the ultrasonic treatment, 4 parts of boron nitride nanosheets and 0.5 parts of dispersant were added thereto, and ultrasonic dispersion was performed for 15 minutes. After the ultrasonic treatment, 2 parts of silicon carbide whiskers and 0.5 parts of dispersant were added thereto, and ultrasonic dispersion was performed for 15 minutes. After the ultrasonic treatment, stirring and dispersion were continued for 2 hours to obtain a waterborne polyurea coating.

[0086] Comparative Example 9

[0087] The difference between this comparative example and Example 1 is that the mixing method of the mixed filler and the polyurea emulsion is different. The specific preparation is as follows:

[0088] S1 filler modification:

[0089] S100: Weighing boron nitride nanosheets and aluminum nitride nanoparticles respectively, adding a solvent to them to disperse them, adding a silane coupling agent to them after dispersion, ultrasonicating them, heating and stirring to react after the ultrasonication, washing and drying to obtain modified boron nitride nanosheets and modified aluminum nitride nanoparticles;

[0090] Specifically, 1g of boron nitride nanosheets and 1g of aluminum nitride nanoparticles are weighed respectively. The thickness of the boron nitride nanosheets is 50-400nm and the size is 500nm; the diameter of the aluminum nitride nanoparticles is 50-100nm. The boron nitride nanosheets and aluminum nitride nanoparticles are respectively put into a flask, 100ml of ethanol solution is added to the flask, and 0.1g of silane coupling agent is added respectively after ultrasonic dispersion for 5min. In this embodiment, the silane coupling agent is 3-aminopropyltriethoxysilane. After ultrasonication for 30min at room temperature, the temperature is heated to 60°C, and the reaction is stirred for 24h to allow the silane coupling agent to fully react with the boron nitride nanosheets and aluminum nitride nanoparticles. After the reaction is completed, the precipitate is filtered and washed with ethanol and water. After washing, it is dried in a constant temperature drying oven at 60°C for 2h to obtain modified boron nitride nanosheets and modified aluminum nitride nanoparticles, which are recovered for use.

[0091] S200: Weighing silicon carbide whiskers, adding a mixed solvent thereto and stirring until the silicon carbide whiskers are completely dissolved, then dropping diisocyanate thereto and continuing the reaction, and after the reaction is completed, centrifugally washing and drying to obtain modified silicon carbide whiskers;

[0092] Specifically, weigh 0.1g of silicon carbide whiskers into a flask, the length of the silicon carbide whiskers is 10-20μm, and the diameter is 500-1000nm. Add 15ml of water and 35ml of acetone to the flask, disperse it by ultrasonic for 5min and keep stirring. Raise the temperature to 30°C, drip 1.5g of IPDI at a rate of 1 drop / s while stirring, and keep reacting for 8h after the addition is completed. After the reaction is completed, collect the precipitate by centrifugation, wash it with a water / acetone mixed solution, and dry it in a 70°C constant temperature oven for 48h to obtain the modified silicon carbide whiskers for use.

[0093] S2: preparing a polyurea emulsion: weighing a polyetheramine, adding a solvent thereto to dissolve it, dropping a diisocyanate thereto to react, and after the reaction is completed, dropping a chain extender and a capping agent thereto and continuing the reaction to obtain an aqueous polyurea emulsion;

[0094] Specifically, 0.01 mol of polyetheramine was weighed and added to a flask, 10 ml of acetone solution was added to the flask, and IPDI was added to the flask under a nitrogen atmosphere at room temperature, with a drop rate of 2 s / drop, and a total amount of 0.02 mol. The reaction was stirred at 5 ° C for 30 min, and the -NCO content was tested and sampled to meet the standard, and then the chain extender was added thereto, with a drop rate of 2 s / drop, and a total amount of 0.005 mol. In this embodiment, diethyltoluenediamine was selected as the chain extender, and 0.01 mol of isocyanate ethyl acrylate was added thereto after the -NCO content was tested and met the standard, and the reaction was continued until the -NCO content reached the standard value, and water was added to the high-speed shear for 2 h and the acetone was removed by rotary evaporation to obtain a polyurea emulsion.

[0095] S3: Prepare coating: Weigh polyurea emulsion, add modified aluminum nitride nanoparticles and dispersant thereto, and then ultrasonically treat. Then, add modified boron nitride nanosheets and dispersant thereto, and then ultrasonically treat. Finally, add modified silicon carbide whiskers and dispersant thereto, and then ultrasonically treat. After the ultrasonic treatment, continue stirring to obtain a waterborne polyurea coating.

[0096] Specifically, 87.5 parts of aqueous polyurea emulsion were weighed, 5 parts of modified aluminum nitride nanoparticles, 4 parts of modified boron nitride nanosheets, 2 parts of modified silicon carbide whiskers and 1.5 parts of dispersant were added thereto, and then ultrasonic dispersion was performed for 60 minutes. After the ultrasonic dispersion was completed, stirring and dispersion were continued for 2 hours to obtain an aqueous polyurea coating.

[0097] The experimental data of the above embodiments and comparative examples are listed in Table 1 below:

[0098] Table 1: Summary of experimental parameters of embodiments and comparative examples

[0099]

[0100] The coatings prepared in the above embodiments and comparative examples were subjected to performance tests, including contact angle test, insulation performance test, thermal conductivity test, hardness and wear resistance test. The test results are shown in Table 2 below.

[0101] The contact angle test method is as follows: a copper sheet with a flat surface is selected as the substrate, the surface of the copper sheet is polished with sandpaper and then cleaned several times, then etched with hydrochloric acid solution for 15 minutes and dried for use. The coatings prepared in the examples and comparative examples are coated on the light-transmitting sheet, and the contact angle is tested after drying for 24 hours.

[0102] The insulation performance test is to determine the volume resistivity. Copper sheet is selected as the test sample. The specific detection methods refer to GB / T 31838.2-2019.

[0103] The thermal conductivity test is to determine the thermal conductivity, and a laser thermal conductivity meter is used to determine the thermal conductivity.

[0104] The hardness and wear resistance test is used to determine the hardness and wear resistance of the coating. The hardness test method refers to GB / T6739-2022; the wear resistance is tested by rubbing the coating with sandpaper 200 times to test the change in the contact angle of the coating.

[0105] The specific experimental results are shown in Table 2 below:

[0106] Table 2: Performance results of coatings of examples and comparative examples

[0107]

[0108] Experimental results analysis:

[0109] From the above experimental results, it can be seen that the volume resistivity of the coating prepared in the embodiment of the present invention can reach more than 2.8*1013Ω·cm, the contact angle can reach more than 150°, and it has obvious insulation performance and super hydrophobic performance. At the same time, by adding thermal conductive fillers, the thermal conductivity, heat dissipation, wear resistance and hydrophobicity of the prepared coating are further improved.

[0110] Comparative Examples 1 and 2 change the amount of polyetheramine added in the polyurea emulsion. From the experimental data, it can be seen that when the amount of polyetheramine added is too high, the hydrophobicity of the prepared coating decreases. The reason is that the excessively high content of polyetheramine will cause the particle size of the emulsion to increase, thereby affecting the hydrophobicity of the coating. If the amount of polyetheramine added is too small, the fracture growth rate and tensile stress of the coating will decrease significantly, thereby reducing the hardness and wear resistance of the coating.

[0111] Comparative Examples 3 and 4 changed the composition and addition amount of the mixed filler. From the experimental results, it can be seen that when the addition amount of the mixed filler is insufficient, the thermal conductivity, hardness, hydrophobicity and wear resistance of the coating are significantly reduced, indicating that the mixed filler plays a key role in improving the comprehensive performance of the coating. When the addition amount of the mixed filler is too high, the comprehensive performance of the coating is improved at a low level, and the volume resistivity is reduced.

[0112] In Comparative Example 5, no modified silicon carbide whiskers were added, and the coating lacked an important link of the heat conduction channel of the component, resulting in a significant decrease in the thermal conductivity of the coating. At the same time, due to the lack of micron-sized modified silicon carbide whiskers, it is difficult to form a regular micro-nano structure on the surface of the coating after coating, which reduces the hydrophobicity and wear resistance of the coating.

[0113] Comparative Examples 6 and 7 did not add modified boron nitride and modified aluminum nitride respectively, and the thermal conductivity of the prepared coatings decreased significantly. Combined with the data of Comparative Example 5, it can be seen that the lack of these three thermally conductive fillers cannot form a complete thermal conductive network and path.

[0114] In summary, the present invention dopes a variety of micro-nano fillers of different morphologies into the original resin material, including silicon carbide whiskers, boron nitride nanosheets and aluminum nitride nanoparticles. By modifying the three micro-nano fillers, they can be evenly dispersed in the resin material, and rely on the excellent thermal conductivity and insulation coefficient of the fillers to improve the thermal conductivity and insulation properties of the resulting coating. At the same time, the three micro-nano fillers have different sizes and morphologies. The larger silicon carbide whiskers are dispersed in the resin to construct a basic heat conduction path. Nano-scale boron nitride and aluminum nitride can be filled in the silicon carbide whiskers and the resin material, and the mutually dispersed silicon carbide whiskers are connected, and finally a three-dimensional, interconnected heat conduction network is formed, so that the coating has a better heat dissipation effect.

[0115] At the same time, in the present invention, the boron nitride nanosheets and aluminum nitride nanoparticles are modified with hydrophobic groups. When the nanoparticles are dispersed in the polyurea resin, the silane coupling agent can reduce the coating surface energy of the coating, so that the coating has good hydrophobic properties. The size of the silicon carbide whisker modified by IPDI can reach the micron level. When the nano-scale boron nitride nanosheets and aluminum nitride nanoparticles are fully mixed in the resin material containing the silicon carbide whisker, the boron nitride nanosheets and aluminum nitride nanoparticles tend to cover the surface of the silicon carbide whisker modified by IPDI to form a micro-nano layered structure, which can significantly improve the roughness and wear resistance of the coating, increase its static contact angle, make the coating show super hydrophobic properties and improve its wear resistance.

[0116] Finally, the present invention adopts a step-by-step mixing and adding process when preparing the coating, firstly adding small-sized boron nitride nanosheets and aluminum nitride nanoparticles to form a "sea-island structure" in the emulsion, and then adding the silicon carbide whiskers modified with IPDI last, so that the large-sized silicon carbide whiskers act as a bridge to connect the boron nitride nanosheets and the aluminum nitride nanoparticles, thereby ensuring that all fillers can be evenly dispersed in the polyurea emulsion, and can form a complete heat conduction path and a micro-nano layered structure, thereby improving the comprehensive performance of the material.

[0117] The beneficial effect of the present invention is that, compared with the prior art,

[0118] 1) The present invention dopes a variety of micro-nano fillers of different morphologies into the original resin material, including silicon carbide whiskers, boron nitride nanosheets and aluminum nitride nanoparticles. By modifying the three micro-nano fillers, they can be evenly dispersed in the resin material, and rely on the excellent thermal conductivity and insulation coefficient of the fillers to improve the thermal conductivity and insulation properties of the resulting coating. At the same time, the three micro-nano fillers have different sizes and morphologies. The larger silicon carbide whiskers are dispersed in the resin to construct a basic thermal conduction path. Nano-scale boron nitride and aluminum nitride can be filled in the silicon carbide whiskers and the resin material, and the mutually dispersed silicon carbide whiskers are connected, finally forming a three-dimensional, interconnected thermal conduction network, so that the coating has a better heat dissipation effect.

[0119] 2) In the present invention, the boron nitride nanosheets and aluminum nitride nanoparticles are modified with hydrophobic groups. When the nanomaterials are dispersed in the polyurea resin, the silane coupling agent can reduce the coating surface energy of the coating, so that the coating has good hydrophobic properties. The size of the silicon carbide whiskers modified by diisocyanate can reach the micron level. When the nano-scale boron nitride nanosheets and aluminum nitride nanoparticles are fully mixed in the resin material containing silicon carbide whiskers, the boron nitride nanosheets and aluminum nitride nanoparticles tend to cover the surface of the silicon carbide whiskers modified by diisocyanate to form a micro-nano layered structure, which can significantly improve the roughness and wear resistance of the coating, increase its static contact angle, make the coating exhibit super hydrophobic properties and improve its wear resistance.

[0120] 3) The present invention adopts a step-by-step mixing and adding process when preparing the coating. First, small-sized boron nitride nanosheets and aluminum nitride nanoparticles are added to form a "sea-island structure" in the emulsion, and then the silicon carbide whiskers modified with diisocyanate are added last, so that the large-sized silicon carbide whiskers act as a bridge to connect the boron nitride nanosheets and aluminum nitride nanoparticles, thereby ensuring that all fillers can be evenly dispersed in the polyurea emulsion, and can form a complete heat conduction path and micro-nano layered structure, thereby improving the comprehensive performance of the material. At the same time, the thermal conductivity and wear resistance of the coating can be improved with less filler material, and the electrical insulation performance of the coating is not lost, thereby reducing the production cost of the coating.

[0121] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents, and any modifications or equivalent replacements that do not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A thermally conductive and insulating water-based polyurea coating, characterized in that: The water-based polyurea coating comprises the following raw materials in parts by weight: 83 to 91 parts of polyurea emulsion, 8 to 15 parts of mixed filler and 1 to 2 parts of dispersant; The polyurea emulsion comprises: polyetheramine, diisocyanate, chain extender and end-capping agent, wherein the molar mass ratio of the polyetheramine, diisocyanate, chain extender and end-capping agent is 1.5-2.5:4:1:2; The mixed filler comprises: modified silicon carbide whiskers, modified boron nitride nanosheets and modified aluminum nitride nanoparticles; The mass ratio of modified silicon carbide whiskers, modified boron nitride nanosheets and modified aluminum nitride nanoparticles added in the mixed filler is 1-4:3-5:4-6; The modified silicon carbide whiskers have a length of 10 to 20 μm and a diameter of 500 to 1000 nm; The boron nitride nanosheets in the modified boron nitride nanosheets have a thickness of 50 to 200 nm and a sheet diameter of 500 nm to 2 μm; The diameter of the aluminum nitride nanoparticles in the modified aluminum nitride nanoparticles is 50 to 100 nm; The modified material of the modified silicon carbide whisker is any one of toluene diisocyanate, 4,4' diphenylmethane diisocyanate or isophorone diisocyanate, or a combination of two or more thereof; The modified material of the modified boron nitride nanosheets and modified aluminum nitride nanoparticles is a silane coupling agent, and the silane coupling agent is one of γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, and γ-aminoethylaminopropyltrimethoxysilane, or a combination of two or more thereof.

2. The thermally conductive and insulating water-based polyurea coating according to claim 1, characterized in that: The diisocyanate is any one of toluene diisocyanate, 4,4' diphenylmethane diisocyanate or isophorone diisocyanate, or a combination of two or more thereof; The chain extender is any one of diethyltoluenediamine, 3,3'-dichloro-4,4'-diaminodiphenylmethane, dimethylthiotoluenediamine, and N,N'-dialkylmethyldiamine; The blocking agent is any one of ethyl isocyanate acrylate or pentaerythritol triacrylate.

3. A method for preparing a thermally conductive insulating waterborne polyurea coating, based on a thermally conductive insulating waterborne polyurea coating according to any one of claims 1 to 2, characterized in that: The following steps are involved: S1 filler modification: weigh boron nitride nanosheets, aluminum nitride nanoparticles and silicon carbide whiskers and put them into a container, and react under set conditions to obtain modified boron nitride nanosheets, modified aluminum nitride nanoparticles and modified silicon carbide whiskers; S2: preparing polyurea emulsion: weighing polyetheramine into a container, adding solvent to dissolve, then dropping diisocyanate to react, and then dropping chain extender and end-capping agent to the container after the reaction is completed and continuing the reaction to obtain polyurea emulsion; S3: Prepare coating: weigh polyurea emulsion into a container, add modified aluminum nitride nanoparticles and dispersant, and then ultrasonically treat, then add modified boron nitride nanosheets and dispersant, and then ultrasonically treat, finally add modified silicon carbide whiskers and dispersant, and then ultrasonically treat, after the ultrasonic treatment is completed, continue stirring to obtain a water-based polyurea coating.

4. The method for preparing a thermally conductive and insulating waterborne polyurea coating according to claim 3, characterized in that: Step S1 specifically includes: S100: Weighing boron nitride nanosheets, aluminum nitride nanoparticles and a silane coupling agent, adding a solvent thereto for ultrasonic dispersion, heating and stirring after the ultrasonic dispersion ends, washing and drying after the reaction ends to obtain modified boron nitride nanosheets and modified aluminum nitride nanoparticles; S200: Weigh silicon carbide whiskers, add a mixed solvent thereto and stir until the silicon carbide whiskers are completely dissolved, then drop diisocyanate thereto and continue the reaction, and after the reaction is completed, centrifuge, wash and dry to obtain modified silicon carbide whiskers.

5. The method for preparing a thermally conductive and insulating waterborne polyurea coating according to claim 4, characterized in that: In the step S100, the solvent is 50% ethanol, the ultrasonic time is 20 to 30 minutes, the stirring temperature is 55 to 65°C, the stirring time is 12 to 24 hours, the drying temperature is 55 to 65°C, and the drying time is 12 to 24 hours; in the step S200, the mixed solvent is water and acetone, the reaction temperature is 30 to 35°C, and the reaction time is 30 minutes to 45 minutes.

6. The method for preparing a thermally conductive and insulating waterborne polyurea coating according to claim 3, characterized in that: In the step S2, the isophorone diisocyanate is added at a rate of 1 to 2 s / drop, the reaction temperature is 0 to 10° C., and the reaction time is 30 to 60 min; The chain extender dropping speed is 1-2s / drop, the reaction temperature is 0-10°C, and the reaction time is 30-60min.

7. The method for preparing a thermally conductive and insulating waterborne polyurea coating according to claim 3, characterized in that: In step S3, the ultrasonic time is 15 to 30 minutes, and the stirring reaction time is 1 to 2 hours.

Citation Information

Patent Citations

  • High heat conduction and dissipation coating and preparation method thereof

    CN104693968A

  • Water-based polyurethane functional coating material and preparation method thereof

    CN105153906A

  • Aqueous acrylate heat-conduction coating material and preparation method thereof

    CN106336759A

  • Boron nitride nanosheet enhanced heat conductive insulating waterborne coating as well as preparation and use methods thereof

    CN107641424A

  • A high thermal conductivity and insulating water-based coating

    CN109181511B

Cited By

  • Transparent weather-resistant polyurea waterproof coating

    CN120484649A

  • Zirconium oxide-graphene composite filler as well as preparation method and application thereof

    CN122037648A